The State of Higher Education in Occupational Health and Safety in Central Asian Countries - Kenesh O. Dzhusupov; Cholpon T. Sulaimanova; Karlygash K. Toguzbayeva; Ramin Tabibi; Bakhtiyar Serik; Cholpon K. Chonbasheva; Khusseyn Egamnazarov; Maigul S. Kainarbayeva (Ubiquity Press, 2018)
A healthy workforce is vital for the sustainable social and economic development of any country. Assuring occupational health and safety (OHS) depends not only on the passing of quality working legislation and inspection of workplaces, but also on preparation of qualified specialists on OHS. Aimed at assessing of relevance of the content of training at Central Asian universities to the needs in prevention of risks of accidents and injuries and promotion of a preventive culture in the workplace, and finding out how they are compliant with the recommendations of the Mainstreaming occupational safety and health into the education (2010), we examined curricula of 20 medical and non-medical universities across Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan. The analysis of training programs showed that education in OHS and preparation of qualified specialists in Central Asiana countries is up-to-date and tailored to local needs for prevention of risks of accidents and injuries and promotes the notion of a preventive culture in the workplace.